A Techno-Economic Feasibility Analysis of an Autonomous Hybrid Renewable Energy Sources for University Building at Saudi Arabia - Tazay, Ahmad F.; Samy, M. M.; Barakat, Shimaa (Journal of electrical engineering & technology, 2020)
The objective of this treatise is to provide a detailed feasibility analysis of the hybrid renewable energy system (HRES) to supply sufficient energy to an autonomous college’s building et al. Baha University in the Kingdom of Saudi Arabia (KSA). The feasibility analysis presents technical and economic guises for the HRES which includes integrated sources of photovoltaic (PV), wind turbine, fuel cell, and batteries. The utilized real data of the island-building is gathered to support the feasibility analysis of the suggested system which includes monthly load consumption, climate data, and installation available space. The sensitivity analysis and the simulation consequences show that the hydrogen energy system reduces the support of the economic and the ecological factors for the HRES comparing with other resources. PV system also plays a considerable influence on the net present cost and the cost of energy of the system.